2021
DOI: 10.34067/kid.0000362021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Patients with Hospital-Recorded Nephrotic Syndrome and Patients with Nephrotic Proteinuria and Hypoalbuminemia: A Nationwide Study in Denmark

Abstract: Background: Registry-based studies of nephrotic syndrome (NS) may only include a subset of patients with biochemical features of NS. To address this, we compared patients with laboratory-recorded nephrotic proteinuria and hypoalbuminemia to patients with hospital-recorded NS. Methods: We identified adult patients with first-time hospital-recorded NS (inpatients, outpatients or emergency room visitors) in the Danish National Patient Registry and compared them to adults with first-time recorded nephrotic protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…First, we relied on recorded diagnoses to identify first-time NS, potentially overlooking NS patients without a diagnosis code specific to NS. 46 Furthermore, less severe events of VTE may have been diagnosed and recorded in NS patients than in the general population, which would lead to overestimating the association between NS and VTE. However, guidelines do not recommend screening asymptomatic NS patients for VTE by radiological examination.…”
Section: Discussionmentioning
confidence: 99%
“…First, we relied on recorded diagnoses to identify first-time NS, potentially overlooking NS patients without a diagnosis code specific to NS. 46 Furthermore, less severe events of VTE may have been diagnosed and recorded in NS patients than in the general population, which would lead to overestimating the association between NS and VTE. However, guidelines do not recommend screening asymptomatic NS patients for VTE by radiological examination.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin in urine, typically quantified as the urine albumin to creatinine ratio (uACR), is present as a continuous variable ranging from very low in healthy individuals to high fractions (e.g., > 30mg/g microalbuminuria, > 300mg/g macroalbuminuria) in nephrotic syndrome [ 1 , 2 ]. Albuminuria is independently associated with increased incidence of cardiovascular events after consideration of traditional risk factors such as high body mass index (BMI), nicotine use, diabetes, and hypertension [ 3 – 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, Vestergaard et al compared patients with biochemical features of NS to patients with hospital-recorded NS within the Danish National Patient Registry in Denmark from 2004–2018 (3). The authors hypothesized that more patients would be identified by laboratory criteria than coded diagnoses.…”
mentioning
confidence: 99%